2017
DOI: 10.4067/s0718-58392017000400413
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory rearing methods that promote inbreeding have a negative impact on the fitness of Mastrus ridens Horstmann (Hymenoptera: Ichneumonidae), a parasitoid used to control the codling moth

Abstract: 413Classical and augmentation biological control depend on the successful laboratory rearing of natural enemies, but rearing methods can affect the success and productivity of a laboratory colony. One process that can occur during rearing is the loss of genetic variability due to inbreeding. The aim of this study was to examine the influence of rearing methods with and without inbreeding in Mastrus ridens Horstmann, a hymenopteran parasitoid specialist of the codling moth (Cydia pomonella [L.]), on several fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The parasitism, fecundity, and sex ratio are some of the most relevant factors when rearing parasitoid wasps [ 51 ]. Our results showed that the PSN and black SN did not have significant effects on the parasitism.…”
Section: Discussionmentioning
confidence: 99%
“…The parasitism, fecundity, and sex ratio are some of the most relevant factors when rearing parasitoid wasps [ 51 ]. Our results showed that the PSN and black SN did not have significant effects on the parasitism.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the factor 'generation' on the development time of M. anticarsiae indicates that the laboratory culture procedure needs improvements in order to avoid negative effects on the parasitoid development as reported by Bueno, Romero, Osorio, and Zaviezo (2017) for Mastrus ridens Horstmann (Hymenoptera: Ichneumonidae), because there were no introduced new parasitoids to the laboratory culture due to the lack of larvae in soybean crops in the field and laboratory. Using wind tunnels to help parasitoids finding the hosts, as well as olfactometers to determine the age of females to mate, could be instruments used to achieve such improvements.…”
Section: Sex Ratio and Development Time Of M Anticarsiae Parasitizinmentioning
confidence: 99%
“…Island populations especially, which can be small given the constrained size of their habitat, experience strong inbreeding depression (Frankham, 1998). Often those agents are hampered by inbreeding depression (Fauvergue et al, 2015;Bueno et al, 2017;Zaviezo et al, 2018), but not always (Trevisan et al, 2016;Quaglietti et al, 2017). Often those agents are hampered by inbreeding depression (Fauvergue et al, 2015;Bueno et al, 2017;Zaviezo et al, 2018), but not always (Trevisan et al, 2016;Quaglietti et al, 2017).…”
Section: Implications For Biological Controlmentioning
confidence: 99%
“…Several groups have studied biocontrol systems with a focus on hymenopterans, many with complimentary sex determination. Often those agents are hampered by inbreeding depression (Fauvergue et al, 2015;Bueno et al, 2017;Zaviezo et al, 2018), but not always (Trevisan et al, 2016;Quaglietti et al, 2017). Low fitness in biocontrol agents in introduced populations relative to native ones, as in Aphidius ervi (Haliday) (Hufbauer, 2002), might be explained by fixation of deleterious alleles through either drift or inbreeding during the introduction.…”
Section: Implications For Biological Controlmentioning
confidence: 99%